A major role of TWEAK/Fn14 axis as a therapeutic target for post-angioplasty restenosis - Nerea Méndez-Barbero (EBioMedicine, 2019)
Background: Tumor necrosis factor-like weak inducer of apoptosis (Tnfsf12; TWEAK) and its receptor Fibroblast growth factor-inducible 14 (Tnfrsf12a; Fn14) participate in the inflammatory response associated with vascular remodeling. However, the functional effect of TWEAK on vascular smooth muscle cells (VSMCs) is not completely elucidated. Methods: Next generation sequencing-based methods were performed to identify genes and pathways regulated by TWEAK in VSMCs. Flow-citometry, wound-healing scratch experiments and transwell migration assays were used to analyze VSMCs proliferation and migration. Mouse wire injury model was done to evaluate the role of TWEAK/Fn14 during neointimal hyperplasia. Findings: TWEAK up-regulated 1611 and down-regulated 1091 genes in VSMCs. Using a gene-set enrichment method, we found a functional module involved in cell proliferation defined as the minimal network connecting top TWEAK up-regulated genes. In vitro experiments in wild-type or Tnfrsf12a deficient VSMCs demonstrated that TWEAK increased cell proliferation, VSMCs motility and migration. Mechanistically, TWEAK increased cyclins (cyclinD1), cyclin-dependent kinases (CDK4, CDK6) and decreased cyclin-dependent kinase inhibitors (p15lNK4B) mRNA and protein expression. Downregulation of p15INK4B induced by TWEAK was mediated by mitogen-activated protein kinase ERK and Akt activation.Tnfrsf12a or Tnfsf12 genetic depletion and pharmacological intervention with TWEAK blocking antibody reduced neointimal formation, decreasing cell proliferation, cyclin D1 and CDK4/6 expression, and increasing p15INK4B expression compared with wild type or IgG-treated mice in wire-injured femoral arteries. Finally, immunohistochemistry in human coronary arteries with stenosis or in-stent restenosis revealed high levels of Fn14, TWEAK and PCNA in VSMCs enriched areas of the neointima as compared with healthy coronary arteries. Interpretation: Our data define a major role of TWEAK/Fn14 in the control of VSMCs proliferation and migration during neointimal hyperplasia after wire injury in mice, and identify TWEAK/Fn14 as a potential target for treating in-stent restenosis. Fund: ISCiii-FEDER, CIBERCV and CIBERDEM. Keywords: Restenosis, Proliferation, Cyclins, TWEAK, Fn14